CMOS-MEMS PIEZOELECTRIC ENERGY HARVESTING SYSTEM - SUHAIDIN, SITI NURHAKMI (Universiti Teknologi Petronas, 2011)
This paper reports a low-cost, high-sensitivity CMOS-MEMS piezoelectric energy harvester with large proof mass. Piezoelectric has known to be the best in harvesting ambient vibration energy. Its simple theory to produce voltage with stress and vibration has come to many optimization researches to produce the best structure with low natural frequency and high yield strength. Four common materials have been compared to see the performance of generating the voltage output. Zinc Oxide, ZnO thin film was utilized as the best piezoelectric material and device was designed using the infamous cantilevered-beam structure which known as the best structure to produce high sensitivity of vibration and has the highest stress effect at the beam tip attached to the stator comb or fixed end. This structure is indeed compatible with CMOS-MEMS fabrication. The structure has been designed and simulated. The device has a sensitivity of I 13.4 J!VIg and the structure has been carefully optimized to avoid structured damage due to undesired mode by incorporating the parallel beam to the cantilever-based structure.